(untitled) (Bioscience Journal, 2018)
The successive use of Roundup Ready crops may difficult the management of volunteer plants originated from seed losses during harvest. In soybean, volunteer corn plants can exhibit higher interference and cause reduce yield depending on their density. The aim of this study was to quantify the economic threshold level (ETL) in soybean as a function of the competition of volunteer corn and to evaluate the chemical control in different phenological stages of development. The ETL and chemical control experiments were conducted in the field, under completely randomized and randomized block designs with one and three replicates, respectively. The variables analyzed were yield and ETL as functions of the competition of different volunteer corn populations (control, 1, 2, 4, 6, 8, 10, 12, 16, 20, 24 and 32 plants m-2) and the chemical control with acetyl coenzyme-A carboxylase (ACCase) inhibitor herbicides alone or mixed with glyphosate in different phenological stages of development (V2-V3, V4-V5 and V6-V8) that were evaluated at seven, 14 and 21 days after application (DAA). The results showed higher competitive potential of volunteer corn in which the presence of one plant m-2 reduces the soybean yield in 17%. The ETL ranged from 0.14 to 0.78 plants m-2 and the control of volunteer corn must be carried out in low populations. The use of ACCase inhibitors herbicides alone or mixed with glyphosate demonstrated greater than 85% control in the V2-V3 phenological stage independent of the period evaluated. The effectiveness of all herbicides decreased with application delay with a control level above 87%, in the V6-V8 phenological stage, obtained only for fluazifop and haloxyfop herbicides alone or in mixed with glyphosate at 14 and 21 days after application.